2002
DOI: 10.1159/000065268
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barré Syndrome Associated with Minimal Change Glomerulopathy and Tubular Dysfunction – Related to Acetone-Based Organic Solvent?

Abstract: A 55-year-old woman presented with Guillain-Barré syndrome, nephrotic syndrome and multiple tubular dysfunction under occupational exposure to an organic solvent, which contained acetone as the principal solvent. In this case, the onset of the nephrotic syndrome and tubular dysfunction coincided with the development of the neurological manifestation. Renal biopsy demonstrated minimal change glomerulopathy with moderate tubulointerstitial nephritis. Several clearance tests that evaluated tubular transport funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We used the key words “proteinuria”, “nephrotic syndrome”, “membranous glomerulonephritis”, “focal segmental glomerulosclerosis” or “minimal change disease” on one side and “Guillain–Barré syndrome”, “acute inflammatory demyelinating polyneuropathy”, “chronic inflammatory demyelinating polyneuropathy” or “neuropathy” on the other. In addition, references cited by the articles produced by the literature search and the present case were included; a total of 33 cases were analyzed . We provisionally classified the 33 cases by the temporal course of disease as follows: GBS, duration to nadir was within 4 weeks and no relapse; and CIDP, duration to nadir was 8 weeks or more and/or relapses.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…We used the key words “proteinuria”, “nephrotic syndrome”, “membranous glomerulonephritis”, “focal segmental glomerulosclerosis” or “minimal change disease” on one side and “Guillain–Barré syndrome”, “acute inflammatory demyelinating polyneuropathy”, “chronic inflammatory demyelinating polyneuropathy” or “neuropathy” on the other. In addition, references cited by the articles produced by the literature search and the present case were included; a total of 33 cases were analyzed . We provisionally classified the 33 cases by the temporal course of disease as follows: GBS, duration to nadir was within 4 weeks and no relapse; and CIDP, duration to nadir was 8 weeks or more and/or relapses.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…One of these patients had his disease after an exposure to organic solvent, principally composed of acetone. Studies have suggested that exposure to organic solvents is associated with glomerular nephropathies and tubular dysfunction, but this relationship remains controversial [8]. A large case-control study of NS with minimal change nephropathy, focal and segmental hyalinosis, and IgA nephropathy demonstrated a clear association between chronic renal failure and high exposure to solvents [9].…”
Section: Case Reportmentioning
confidence: 99%